2014
DOI: 10.1002/eji.201444719
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia in the intestine or solid tumors: A beneficial or deleterious alarm signal?

Abstract: IntroductionThe availability of oxygen in the atmosphere provided protozoans with the ability to meet higher energy demands required for the development of complex multicellular organisms. Consequently, oxygen-dependent cells developed mechanisms to sense and adapt to changes in oxygen levels [1]. In mammals the respiratory, circulatory and nervous system work together to ensure that oxygen levels are precisely maintained, because excess or deficiency of oxygen can lead to cell death and tissue damage [2].The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 66 publications
(93 reference statements)
0
20
0
Order By: Relevance
“…Hypoxia is one of the typical biological phenomena that plays a key role in the growth and invasiveness of a wide variety of solid tumors including lung cancer [7]. Numerous studies documented that the hypoxia microenvironment was able to enhance tumor progression [9,15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hypoxia is one of the typical biological phenomena that plays a key role in the growth and invasiveness of a wide variety of solid tumors including lung cancer [7]. Numerous studies documented that the hypoxia microenvironment was able to enhance tumor progression [9,15].…”
Section: Discussionmentioning
confidence: 99%
“…Hypoxia is a typical phenomenon of solid tumors because of the imbalance between oxygen consumption and oxygen supply [7]. Accumulating evidence has indicated that the hypoxia microenvironment promotes the growth and metastasis of lung cancer cells [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…It is noteworthy that HIF-1α may also exert regulatory effects in normoxia, in particular during bacterial infection, where HIF-1α expression is stimulated through TLR receptor engagement and cell signaling pathways (such as NF-κB and MAPK) [for review see Ref. ( 53 )].…”
Section: Macrophage Polarization Is Associated To a Shift Of Metabolimentioning
confidence: 99%
“…Hypoxia-inducible factor-1 (HIF-1) plays a central role in these processes. 3 HIF-1 is a heterodimer that consists of two subunits: HIF-1α and HIF-1β. HIF-1β is constitutively expressed, whereas HIF-1α is a cytoplasmic protein that responds to oxygen levels.…”
Section: Introductionmentioning
confidence: 99%